ANALYSIS OF THE CONCEPT OF SINCERITY IN THE BOOK NASHAIHUL ‘IBAD AND ITS RELEVANCE TO THE ETHICS OF CHARITY (WORSHIP AND CONTENT) ON SOCIAL MEDIA OF GENERATION Z IN THE DIGITAL ERA - Safinatul A Yun; M. Fauzi (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
Sincerity is one of the fundamental values ​​in Islamic teachings, interpreted as an effort to purify intentions from all forms of riya (showing off), ujub (showing off), and worldly interests so that every deed is solely directed to Allah SWT. This concept is explained in depth in Nashaihul ‘Ibad, which emphasizes the importance of purity of heart in every form of worship and human behavior. From a Sufi perspective, sincerity is not only understood as a spiritual dimension, but also as a moral foundation that determines the quality of one’s deeds before Allah. However, the development of the digital era has presented new challenges in implementing the value of sincerity, especially for Generation Z who grew up and developed amidst social media culture. Generation Z is known as a generation that is very active in the digital space through various platforms such as Instagram, TikTok, YouTube, and X. Religious activities that were previously personal are now tending to shift to become more open and performative. Phenomena such as sharing worship activities, alms, studies, and religious content are often accompanied by an orientation towards social validation in the form of likes, views, comments, and followers. This condition can influence the orientation of intentions in deeds, thus giving rise to the potential for digital riya (showing off) and the search for public recognition. Therefore, this study aims to analyze the concept of sincerity in Nashaihul ‘Ibad and its relevance to the ethics of charity and content for Generation Z in the digital era. This aims to develop a digital ethic grounded in Islamic spiritual values ​​and strengthen contemporary Sufism studies.